The CHESS Protocol: A Mixed-Methods Evaluation of an HPV Screening Intervention for Women Living With HIV in Nigeria - Olabanjo Ogunsola; Laura M. Gaydos; Oluseye Ajayi; Maria Dieci; Nadi Kaonga; Olutosin Awolude; Priscilla Ezemelue; Tyree Staple; Kabiru Salami; Ifeoma Idigbe; Oliver Ezechi; Lisa Flowers (International Journal of Public Health)
ObjectivesIn this protocol, we describe a planned intervention to adapt the Mother Mentor (MoMent) peer support program for women living with HIV (WLWH). WLWH face a six-fold higher risk of cervical cancer, yet screening and treatment rates remain low in Nigeria.MethodsUsing an implementation science approach, we will engage key stakeholders—including ministries of health, NACA, professional bodies, WLWH, Mentor Mothers, healthcare providers, and development partners (e.g., WHO, US CDC, USAID)—through deliberative democracy to adapt and expand MoMent for home-based HPV screening and follow-up treatment. We will pilot the adapted MoMent HIV+HCC program with 1,500 women in 15 health facilities across Nigeria’s five geopolitical zones. The RE-AIM framework will guide evaluation of reach, adoption, fidelity, effectiveness, and sustainability.ResultsThis study is designed to contribute to WHO’s global strategy to eliminate cervical cancer by improving access to home-based screening and care in low-resource settings.ConclusionFindings will inform national HPV prevention efforts and may drive broader integration into Nigeria’s cervical cancer program.Clinical Trial RegistrationClinicaltrials.gov, identifier NCT06751030.